Phase separation and gap bowing in zinc-blende InGaN, InAlN, BGaN, and BAlN alloy layers - Teles, L. K.; Furthmuller, J.; Scolfaro, LMR; Tabata, A.; Leite, JR; Bechstedt, F.; Frey, T.; As, D. J.; Lischka, K. (Elsevier B.V., 2002)
We present first-principles calculations of the thermodynamic and electronic properties of the zinc-blende ternary InxGa1-xN. InxAl1-xN, BxGa1-xN, and BxAl1-xN alloys. They are based on a generalized quasi-chemical approximation and a pseudopotential-plane-wave method. T-x phase diagrams for the alloys are obtained, We show that due to the large difference in interatomic distances between the binary compounds a significant phase miscibility gap for the alloys is found. In particular for the InxGa1-xN alloy, we show also experimental results obtained from X-ray and resonant Raman scattering measurements, which indicate the presence of an In-rich phase with x approximate to 0.8. For the boron-containing alloy layers we found a very high value for the critical temperature for miscibility. similar to9000 K. providing an explanation for the difficulties encountered to grow these materials with higher boron content. The influence of a biaxial strain on phase diagrams, energy gaps and gap bowing of these alloys is also discussed. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: InGaN; InAlN; BGaN; BAlN; phase separation